Review of palaeozygopleurid gastropods (Palaeozygopleuridae, Gastropoda) from Devonian strata of the Perunica microplate (Bohemia), with a re-evaluation of their stratigraphic distribution, notes on their ontogeny, and descriptions of new taxa - Frýda, Jiří; Ferrová, Lenka; Frýdová, Barbora (Zootaxa, 2013)
Review of all species of the family Palaeozygopleuridae Horný, 1955 (Gastropoda) known from the Perunica microplate (Bohemia) is presented with a description of three new species, Palaeozygopleura lukesi sp. nov., Cimrmaniela sveraki gen. et sp. nov. and Cimrmaniela smoljaki gen. et sp. nov. The stratigraphic distributions of the most of Bohemian palaeo-zygopleurid species are either corrected or refined, based on new records or modern stratigraphic studies. A complete list of the geographic occurrences of all known palaeozygopleurid gastropods from the Perunica microplate is also given to-gether with notes on their ontogeny.